Cancer‐Cell‐Activated in situ Synthesis of Mitochondria‐Targeting AIE Photosensitizer for Precise Photodynamic Therapy. (31st May 2021) - Wang, Yuanbo; Xu, Shidang; Shi, Leilei; Teh, Cathleen; Qi, Guobin; Liu, Bin
Abstract: Maximization of phototoxic damage on tumor with minimized side effect on normal tissue is essential for effective anticancer photodynamic therapy (PDT). This requires highly cancer‐cell‐specific or even cancer‐cell‐organelle‐specific synthesis or delivery of efficient photosensitizers (PSs) in vitro and in vivo, which is difficult to achieve. Herein, we report a strategy of cancer‐cell‐activated PS synthesis, by which an efficient mitochondria‐targeting photosensitizer with aggregation‐induced‐emission (AIE) feature can be selectively synthesized as an efficient image‐guided PDT agent inside cancer cells. MOF‐199, a Cu II ‐based metal‐organic framework, was selected as an inert carrier to load the PS precursors for efficient delivery and served as a Cu I catalyst source for in situ click reaction to form PSs exclusively in cancer cells. The in situ synthesized PS showed mitochondria‐targeting capability, allowing potent cancer‐cell‐specific ablation under light irradiation. The high specificity of PSs produced in cancer cells also makes it safer post‐treatment. Abstract : Mitochondria‐targeting AIE photosensitizer is specifically synthesized inside cancer cells, realizing precise photodynamic therapy.